Flow-based system for the determination of titratable acidity in wines - Vidigal, Susana S. M. P. (2016)
A flow injection analysis system with a spectrophotometric detection was arranged in order to develop a simple and fast methodology for the quantification of titratable acidity in different types of wines. In the proposed system, a precise volume of sample is injected in the carrier stream, composed by a mixture of OH− solution with the pH indicator, bromothymol blue (BTB). Consequently, a change on the colour of the carrier solution is achieved and quantified by spectrophotometry. Therefore, it was possible to establish a linear range up to 0.16 g/L expressed as tartaric acid, with a limit of detection and quantification of 0.01 and 0.05 g/L, respectively. The proposed work has a low sample and reagents consumption, only 96 μg of BTB, 336 mmol de OH− and 50 μL of sample were needed per assay. At the same time, a high determination rate was achieved, 75 determinations per hour. The developed methodology was applied on the quantification of total acidity in red and white table wine and port wine samples.